Polyphenolic fraction of Lonicera caerulea L. fruits reduces oxidative stress and inflammatory markers induced by lipopolysaccharide in gingival fibroblasts - Galandáková, Adéla; Rajnochová Svobodová, Alena; Chytilová, K; Simánek, V; Ulrichová, J (Food and chemical toxicology, 2010)
The most common oral diseases have a microbial aetiology. Pathogenic bacteria liberate a number of irritating agents including a lipopolysaccharide (LPS) that activates pro-inflammatory cytokines promoting increased activity of polymorphonucleocytes (PMN). Release of PMN-derived free radicals into an infected gingival area affects gums, periodontal ligaments and alveolar bone. Berries of Lonicera caerulea L. (blue honeysuckle) are rich in phenolics, particularly phenolic acids, flavonoids and anthocyanins that have multiple biological activities in vitro and in vivo such as antiadherence, antioxidant and anti-inflammatory. Studies have shown that polyphenols suppress a number of LPS-induced signals and thus could be effective against gingivitis. Here we assessed effects of the polyphenolic fraction of L. caerulea fruits (PFLC; containing 77% anthocyanins) on LPS-induced oxidative damage and inflammation in human gingival fibroblasts. Application of PFLC (10-50mug/ml) reduced reactive oxygen species (ROS) production, intracellular glutathione (GSH) depletion as well as lipid peroxidation in LPS-treated cells. PFLC treatment also inhibited LPS-induced up-regulation of interleukin-1beta (IL-1beta), interleukin-6 (IL-6) and tumour necrosis factor-alpha (TNF-alpha) and it suppressed expression of cyclooxygenase-2 (COX-2). The effects are presumably linked to its antioxidant and anti-inflammatory activities and suggest its use in attenuating the inflammatory process, including periodontal disease.
Keywords: Lonicera; flavonoidy; zánět; Cytokines; lipopolysacharidy; glutathion; biologické markery; oxidační stres; Gingiva; Biomarkers; Glutathione; Fibroblasts; Flavonoids; fenoly; Phenols; Polyphenols; Oxidative Stress; cytokiny; gingiva; lidé; Reactive Oxygen Species; fibroblasty; Lipopolysaccharides; kultivované buňky; Inflammation; Cells, Cultured; reaktivní formy kyslíku; polyfenoly; Humans